2015
DOI: 10.1016/j.jmmm.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Reversal-mechanism of perpendicular switching induced by an in-plane current

Abstract: We propose a magnetization reversal model to explain the perpendicular switching of a single ferromagnetic layer induced by an in-plane current. Contrary to previously proposed reversal mechanisms that such magnetic switching is directly from the Rashba or spin Hall effects, we suggest that this type of switching arises from the current-induced chirality dependent domain wall motion. By measuring the field dependent switching behaviors, we show that such switching can also be achieved between any two multidoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Above the critical value, a domain can still be thought as a uniform magnetization with higher magnetic energy that is unstable under the large current. As demonstrated before, the separate control of V D for two types of DWs can be realized in HM/FM bilayers and V RD depends on the strength of applied in-plane fields [19,20]; therefore, a large enough field is necessary to realize a full SOT switching [2][3][4]27] in these structures.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Above the critical value, a domain can still be thought as a uniform magnetization with higher magnetic energy that is unstable under the large current. As demonstrated before, the separate control of V D for two types of DWs can be realized in HM/FM bilayers and V RD depends on the strength of applied in-plane fields [19,20]; therefore, a large enough field is necessary to realize a full SOT switching [2][3][4]27] in these structures.…”
Section: Discussionmentioning
confidence: 80%
“…It is shown that the SOT switching direction of SAFs can be reversed depending on the strength of applied in-plane fields, even with the same sign of SHA. These results indicate that the switching of SAFs can be achieved without any direction changes of the applied in-plane field and current, contrary to the switching of a single ferromagnet [2][3][4]12,14,18,[23][24][25]27] in which the direction of either current or in-plane field has to be reversed. The observed anomalous magnetization switching (AMS) behaviors invalidate the conventional macrospin model and prompt a new understanding of SOT switching.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, many aspects of SOT switching are still under debate. For example, the origin of SOTs can be spin Hall effects (SHEs) [40][41][42] or Rashba effects [11,43], and their roles during the switching process are still not clear [11,41,42,[44][45][46]. Generally, the SOT switching starts from a reversal domain nucleation in a uniform magnetization state and then the nucleated domains expand to the entire film [44,47,48].…”
Section: Voltage Control Of Sot Switchingmentioning
confidence: 99%
“…Conventional spin transfer torque (STT) utilizes the spin polarized current to transfer angular momentum from one FM to another FM [5,6], and it has been applied to various spintronic devices such as a magnetic random access memory (MRAM) [7][8][9] and race-track domain wall memory [10]. Recently emerging spin-orbit torque (SOT) opens a new prospect in the magnetization manipulation of the HM=FM bilayers [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In a SOT device, the electrons flowing in a HM layer with strong spin-orbit coupling are spin polarized and the subsequent spin current transfers its angular momentum to the adjacent FM.…”
mentioning
confidence: 99%